ASSET REVALUATION AS A MODERATION VARIABLE FACTORS THAT AFFECT THE VALUE OF THE COMPANY - Khofifah, Fitri; Widyastuti, Emy (Jurnal Al-Iqtishad, 2024)
This study aims to determine the effect of Liability, Investment Opportunity Set and Fixed Asset Intensity on Firm Value with Asset Revaluation as a moderating variable. The case study was conducted on manufacturing companies listed in the Jakarta Islamic Index (JII) for the 2017-2021 period. This study uses a quantitative approach with a population of 8 manufacturing companies whose shares are listed in the JII. The sample used was 40 selected through the Purposive Sampling method. This study uses secondary data analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results of the study indicate that liability has a positive insignificant effect on firm value, Investment Opportunity Set has a positive significant effect on firm value, Fixed Asset Intensity has a negative insignificant effect on firm value, asset revaluation cannot moderate liability, Investment Opportunity Set and Fixed Asset Intensity on firm value